Altered expression of inflammation-associated molecules in striatum: an implication for sensitivity to heavy ion radiations - Chen, Zixuan; Li, Yumeng; Rasheed, Madiha; Wang, Hao; Lei, Runhong; Zhao, Tuo; Deng, Yulin; Ma, Hong (Frontiers in Cellular Neuroscience, 2023)
Background and objective Heavy ion radiation is one of the major hazards astronauts face during space expeditions, adversely affecting the central nervous system. Radiation causes severe damage to sensitive brain regions, especially the striatum, resulting in cognitive impairment and other physiological issues in astronauts. However, the intensity of brain damage and associated underlying molecular pathological mechanisms mediated by heavy ion radiation are still unknown. The present study is aimed to identify the damaging effect of heavy ion radiation on the striatum and associated underlying pathological mechanisms. Materials and methods Two parallel cohorts of rats were exposed to radiation in multiple doses and times. Cohort I was exposed to 15 Gy of 12C6+ ions radiation, whereas cohort II was exposed to 3.4 Gy and 8 Gy with 56Fe26+ ions irradiation. Physiological and behavioural tests were performed, followed by 18F-FDG-PET scans, transcriptomics analysis of the striatum, and in-vitro studies to verify the interconnection between immune cells and neurons. Results Both cohorts revealed more persistent striatum dysfunction than other brain regions under heavy ion radiation at multiple doses and time, exposed by physiological, behavioural, and 18F-FDG-PET scans. Transcriptomic analysis revealed that striatum dysfunction is linked with an abnormal immune system. In vitro studies demonstrated that radiation mediated diversified effects on different immune cells and sustained monocyte viability but inhibited its differentiation and migration, leading to chronic neuroinflammation in the striatum and might affect other associated brain regions. Conclusion Our findings suggest that striatum dysfunction under heavy ion radiation activates abnormal immune systems, leading to chronic neuroinflammation and neuronal injury.